SLA-based dynamic resource management in wireless environments: an enterprise nomadism use case. (7th July 2008) - Tebbani, Badis; Aib, Issam; Pujolle, Guy
In this paper, we contribute on the service-driven management of quality of service and user access in wireless corporate networks. We propose a Service-Level Agreement (SLA) oriented nomadism management architecture with a top-down vision starting by the specification of company objectives and going down to device-level configurations. We define an algorithm for the automatic translation of application-level quality assurance parameters into network-level configuration parameters. A prototype implementation of our solution to the SLA-driven enterprise nomadism management is presented along with preliminary results on the self-adaptive capabilities of our QoS mapping algorithm.